Beyond comfort: Oral hygiene as a critical nursing activity in the intensive care unit - Berry, A.; Davidson, Patricia (Churchill Livingstone, 2006)
Background: The role of oral hygiene in maintaining the health and well being of patients in the intensive care unit (ICU) is indisputable. This importance is not reflected in the body of research related to ICU practice. While a number of studies have examined oral hygiene practices in oncological patients there is significantly less attention devoted to these practices in the critically ill. Aim: This paper has two discrete yet interrelated aims. Firstly, in relation to current available evidence and based on a sound knowledge of oral physiology, identify barriers to effective oral hygiene and subsequent effectiveness of the most commonly used and recommended methods of providing oral hygiene in the critically ill population. Secondly, informed by the critical review, identify recommendations for practice and future intervention studies. Findings: To date, there is no definitive evidence to determine the most appropriate method of oral hygiene including the use of beneficial mouth rinses. Barriers identified in this review to providing optimal hygiene include: (1) mechanical barriers and equipment issues, (2) perceptions of the importance of mouth care and empathy with patient discomfort by nurses, (3) altered patient sensory perception and discomfort and (4) difficulties in patient communication. In spite of these challenges opportunities for collaborative research and increasing expertise in nurse researchers creates a climate to derive solutions to these factors. Conclusions: It is clearly evident from this review of oral hygiene practices in intensive care that the need for ongoing research is of paramount importance. ICU nurses undeniably require rigorous research studies in order to inform their practice in the provision of oral hygiene for critically ill patients.